Inoculação de fungos micorrizicos arbusculares e bactérias solubilizadoras de fosfato no desenvolvimento de teca e soja - Della Flora, Larissa Venturini (2020)
In order to increase crop productivity and reduce agricultural inputs, the use of biological inoculants, a highly efficient technology and already adopted for other uses, becomes an important alternative to circumvent the problem of phosphorus in soils. In this work, two plant species were used, one agricultural and one forest with high economic value for both the state and the foreign market. The objective of this work was to evaluate whether the inoculation of isolated microorganisms from northern Mato Grosso (Amazon biome), influence soybean productivity and Teca growth and development in nursery and field conditions (cerrado). For this, 4 isolates of Mycorrhizal Fungi and a solubilizing bacterium were used. In the first study (chapter 2), the use of four morphotypes of arbuscular mycorrhizal fungi (denuded MF1, MF2, MF3, MF4) was tested, isolated from native forest in a tropical region inoculated in 5 commercial Teak clones, evaluating their effect on production of clonal teak seedlings in the nursery and in the initial phase in the field. In the second experiment (chapter 3), an arbuscular mycorrhizal fungus (MF4) and a phosphate solubilizing bacteria (MSB2), both isolated from the Amazon biome, were inoculated in a soybean furrow. The use of the 4 isolates of Mycorrhizal Fungi tested in Teak seedlings, showed promise in increasing the survival of seedlings, reaching rates above 80%, meaning greater seedling production for the nursery. Clone 6 showed greater growth in diameter in the presence of MF1 and MF2 isolates; the other clones did not show significant diameter growth in the present isolates. In height, clones 1 and 3 showed higher growth than seedlings not inoculated in the presence of isolates MF1, MF2 and MF3. It is clearly observed that there is a symbiotic effectiveness relationship between the different clones and the tested fungi, where the effects differ with the interactions. In the field, the seedlings showed no significant difference in development until the present evaluations. In soy, the inoculation of FMA and phosphate fertilization resulted in productivity gains, as well as the inoculation of solubilizing bacteria and phosphate fertilization, that is, an increase in the efficiency of phosphate fertilizers. Isolated inoculation, FMA or bacteria did not show results in both growth and yield factors. These results allow us to conclude that the choice of the most effective fungus with each clone results in higher seedling yield in the nursery, in the field evaluations will be necessary over time. In the soybean culture, the use of inoculation in conjunction with phosphate fertilization increases the efficiency of fertilization in production.